A CACGTG motif of the Antirrhinum majus chalcone synthase promoter is recognized by an evolutionarily conserved nuclear protein. - Staiger, D (1989)
In the chalcone synthase gene of Antirrhinum majus (snapdragon), 150 base pairs of the 5' flanking region contain cis-acting signals for UV light-induced expression. A nuclear factor, designated CG-1, specifically recognizes a hexameric motif with internal dyad symmetry, CACGTG, located within this light-responsive sequence. Binding of CG-1 is influenced by C-methylation of the CpG dinucleotide in the recognition sequence. CG-1 is a factor found in a variety of dicotyledonous plant species including Nicotiana tabacum, A. majus, Petunia hybrida, Arabidopsis thaliana, and Glycine max. CACGTG motifs contained within trans-acting factor recognition sites in various other plant promoters can interact with CG-1. In addition, the binding site of the human adenovirus major late transcription factor USF can compete for CG-1 binding to the chalcone synthase promoter. This suggests an evolutionary conservation of trans-acting factor recognition sites involved in divergent mechanisms of gene control.